Using Digital Mind Mapping to Improve Writing Skills - Medyana Inna Sairo; Ni Made Ratminingsih; I Gede Arya Sudira (Universitas Pendidikan Ganesha, 2021)
There are still many students who lack writing skills. Students are confused about starting a discussion or determining ideas, and the lack of vocabulary makes it difficult for students to write. This study aims to analyze the use of digital mind mapping to improve students' writing skills. This type of research is classroom action research which will be divided into two cycles. cycle 1 in 3 sessions and cycle 2 in 2 sessions. The research subjects were 33 students. The methods used in collecting research data are observation, interviews, and tests. The instruments used to collect data are questionnaires and test sheets. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results showed that Digital Mind Mapping was effective for improving students' abilities. It was found that the average score of students in the pre-test was 24%, increased to 90% in the post-test I and in the post-test II. There was an increase in the number of students who had not previously achieved the KKM. The increase in the average score of students is also supported by student interest during the teaching and learning process because the method uses technology. In addition, the students found that the Digital Mind Mapping activity helped them organize students' ideas, become critical thinking, creative and improve students' writing.